The Use of Over-The-Counter Drugs and Its Health Implications in Awka South LGA, Anambra State, Nigeria - Onyedinefu, Abraham; Osuagwu, Gift Ogechi (MASI Mandiri Edukasi, 2024)
This work examined the use of over-the-counter drugs and its health implications in Awka South LGA of Anambra State, Nigeria. The objective of the study is to empirically interrogate the prevalence of over-the-counter drug use in Awka South LGA of Anambra State, Nigeria; the factors influencing it, and its health implications. The study used a mixed methods research approach, with 204 respondents selected through a multistage sampling procedure. The structured questionnaire and In-Depth Interview (IDI) guide acted as data-gathering tools. The quantitative data were coded and processed with SPSS version 20. Frequency tables were utilized to evaluate, characterize, and show the data, whereas quantitative data were manually transcribed and analyzed using content analysis. Two study hypotheses were developed and tested using chi-square inference statistics. This study revealed that various factors influence the use of OTC drugs in Awka South LGA. The study equally found that the use of OTC drugs is very prevalent in Awka South LGA. Moreover, the study also found that abusing OTC drugs has health implications. Based on these findings, this study recommended that the government should regulate the production, sale, and advertisement of OTC drugs. The study also recommended that sensitization and awareness programs should be carried out periodically to teach people when and when not to use OTC drugs.